2017
DOI: 10.1371/journal.pone.0171704
|View full text |Cite
|
Sign up to set email alerts
|

The presence of the gadolinium-based contrast agent depositions in the brain and symptoms of gadolinium neurotoxicity - A systematic review

Abstract: Background and purposeGadolinium based contrast agents (GBCAs) are widely used in magnetic resonance imaging, but recently, high signal intensity in the cerebellum structures was reported after repeated administrations of contrast- enhanced magnetic resonance images. The aim of this systematic review was to investigate the association between increased signal intensity in the dentate nucleus and globus pallidus in the brain and repeated administrations of GBCAs. Additionally, we focused on possible short- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
117
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(122 citation statements)
references
References 48 publications
1
117
0
1
Order By: Relevance
“…Costs, time required to perform the study, gadolinium-based contrast media potential risk in patients with impaired renal function and its accumulation in the central nervous system represent the major drawbacks of DCE. [40] The value of bpMRI in the detection of PCa using 1.5T MRI with endorectal coil has been reported. [23,41] Recently, it has been demonstrated that the sensitivity of bpMRI at 3T without endorectal coil in the detection PCa is similar to that of mpMRI.…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%
“…Costs, time required to perform the study, gadolinium-based contrast media potential risk in patients with impaired renal function and its accumulation in the central nervous system represent the major drawbacks of DCE. [40] The value of bpMRI in the detection of PCa using 1.5T MRI with endorectal coil has been reported. [23,41] Recently, it has been demonstrated that the sensitivity of bpMRI at 3T without endorectal coil in the detection PCa is similar to that of mpMRI.…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%
“…Thus far, 15 out of 19 studies found a positive correlation between the number of administrations of a linear chelate and the measured signal intensity in the basal ganglia. At this moment, the association has not been demonstrated for the macrocyclic chelates [6,7]. The four contrast agents that the EMA has recommended suspending and/or restricting …”
Section: Evidence For Gadolinium Retentionmentioning
confidence: 92%
“…A T1-weighted MRI acquired post GBCA injection is a part of the recommended MRI protocols for diagnosis and follow-up examinations of MS patients [3]. However, the use of GBCAs has been a recent topic of debate, primarily due to reports of Gd deposition in the brain [4,5]. Suggestions insisting on greater debate before GBCA administration has gained traction due to observed MRI signal changes in the brain tissues due to repeated GBCA administrations and other possible health issues [6].…”
Section: Introductionmentioning
confidence: 99%